Anyonik reaktiflerin sepiyolit tarafından adsorplanma mekanizması - Çınar, Mustafa (Fen Bilimleri Enstitüsü, 1998)
Bu tez çalışması kapsamında sepiyolitin anyonik reaktifleri adsorplama yeteneği ve mekanizması araştırılmıştır. Sepiyolitin adsorpsiyon mekanizmasını belirlemek amacıyla orijinal ve aktive edilmiş sepiyolit yüzeylerine yüzey aktif bir madde olan sodyum dodesilsülfatın (SDS) adsorpsiyonu incelenerek çeşitli şartlarda adsorpsiyon izotermleri elde edilmiştir. Sepiyolitin adsorpsiyon özelliklerini daha iyi yorumlamak amacıyla sepiyolitin pH dengesi çözünürlüğü ve zeta potansiyel davranışı araştırılmıştır. Sepiyolitin pH 8. 5 'da tampon pH oluşturduğu ve pH düştükçe Mg çözünürlüğünün arttığı teyid edilmiştir. Kahverengi sepiyolitin pH'ya göre değişimi, iki farklı katı konsantrasyonunda (%0.2 ve %5) incelenmiş ve sepiyolitin sıfır yük noktaları, %0.2 ve %5 katı konsantrasyonlarında sırasıyla pH=3.2 ve 6.3 olarak elde edilmiştir. Literatürde çok kısıtlı veriler olmasından dolayı kahverengi sepiyolit ile elde edilen sonuçların mukayesesi yapılamamıştır. Sıfır yük noktalarındaki bu farklılık, artan katı konsantrasyonu sonucu süspansiyon içinde artan magnezyum iyon konsantrasyonu ve buna bağlı olarak ortamın artan viskozitesi ile açıklanmaktadır. Sepiyolitin adsorpsiyon özelliklerini araştırmak amacıyla kıvam süresi, katı konsantrasyonu gibi parametrelerin adsorpsiyon yoğunluğuna olan etkileri incelenmiştir. Buna göre optimum katı kınsantrasyonu 50mg/ml, kıvam süresinin ise 2 saat olduğu belirlenmiştir. Orjinal sepiyolitle oda sıcaklığında yapılan deneylerde çözeltiye geçen Mg iyonlarının SDS ile birleşerek Mg(DDS)2 çökeleği oluşturdukları ve bunun da gerçek adsorpsiyon değerini maskelediği tesbit edilmiştir. Çökeleğin etkisini belirlemek için elde edilen abstraksiyon değerlerinden çökelek değerleri çıkartılarak gerçek adsorpsiyon değerleri bulunmuştur. Orijinal sepiyolitle değişik sıcaklıklarda (40 ve 60°C) adsorpsiyon deneyleri yapılmış ve ortam sıcaklığındaki artışa bağlı olarak adsorsiyon yoğunluğunun azaldığı; ayrıca sistemde 25 ve 40 °C ortam sıcaklıklarında Mg(DDS)2 çökeleğinin oluşmasına rağmen 60oC'de çökelek görülmemiştir. pH'a göre yapılan adsorpsiyon deneylerinde adsorpsiyonun pH düştükçe artan çökelekten dolayı azaldığı bulunmuş ve en yüksek adsorpsiyon yoğunluğuna da tabii pH'da ulaşılmıştır. Sepiyolitin asit ve ısıl aktive edilmesi sonucu yüzey alanları orijinal sepiyolitin yüzey alanına göre 4-5 kat artmasına rağmen adsorpsiyon yoğunluğunda artış görülmemiş hatta orijinal sepiyolitin altına düşmüştür. Bu da ısıl ve asit işlemin hem su molekülünün yapısını bozduğunu hem de oktahedral tabakadaki magnezyum bağlantısını koparttığını ve bunun sonucunda da adsorpsiyonun düştüğünü göstermektedir. Katı yüzeyine reaktif adsorpsiyonunun termodinamik esaslarının incelenerek, adsorpsiyon verileri Frumkin, Uyarlanmış Frumkin, Langmuir ve Flory-Huggins modellerine uygulanmış ve bunlardan Uyarlanmış Frumkin modelinin SDS/sepiyolit sistemini en uygun temsil ettiği tesbit edilmiştir. Yapılan hesaplamalar sonucu AG° yaklaşık olarak -3.40Kcal/mol AH0 ise -1.87 Kcal/mol olarak hesaplanmıştır. Bu sonuçlar bize SDS'nin sepiyolit yüzeyine fiziksel olarak adsorplandığını göstermektedir.

Sepiolite belongs to clay family known as sepiolite-palygorskite. In 1913, Fersman applited the term palygorskite, to family of hydrous magnesium silicates forming and isomorphous series between two extreme members; an aluminium extreme called paramontmorillonitte, due to its almost complete similarity to montmorillonite, differing only its fibrous structure and a magnesium extreme called sepiolite. Sepiolite has been known for a long time. As early as 1758, Cronsted described Keffekil Tartarorum, a mineral wich may very well have been sepiolite. Inl801, Holy called it Ecume de Mer. As far as we know Glocker was the first to use the term sepiolite, deriving the new name from the Greek wich means cuttlefish because of the resemblance of its light and porous internale shale or bone to sepiolite. Sepiolite has been used for houndreds of years in the manufacturing of pipes for instance the pipes of Lemgo (Lippe, Germany) manufactured from 1750 to 1912 (Martin Vivaldi, 1971). The sepiolite of Valleras long with Clay from Capadimonte (Prado, 1864) was used in the ceramik-paste required to make the famous porcelein manufactured in "La China" founded in been 1760 by Carlos III of Spain until its destruction by Napoleon's troops in 1808. Seepiolite is presently used in a wide variety of fields which take advantage of the great absorption capacity, rheological behaviour as well as catalytic action of the clay; all of these properties may be improved by various treatments. The applications are based on the following three types of properties.. Sorptive properties. Rheological properties. Catalytic properties The sorption capacity of sepiolite renders it valuable as a bleaching and clarifying agent, filter aid, industrial absorbent and carrier of catalysts as a thickening suspending or thixotropic agent and its diverse applications include a seemingly limitless range of uses from the manufactures of cosmetics to that of paints and even fertilizers. Recently new uses of sepiyolite as catalyst have been reported. Sepiolite is often found associated with other clays and non-clay minerals such as carbonates, quartz, feldspar and phosphates. The most important occurences of sepiolite are found in Vallecas is Spain, Turkey, Madagaskar and Tanzania. The deposits available to industry, however are few. Sepiolite may appear in two forms a sepiolite or parasepiolite, which occurs as large bondles of crystaline fibers, and |3 sepiyolite which occurs as amorphouse aggregates or small flat rounded particles. Sepiolite may adopt a compact or a soft porous macroscopic aspect or less frequently, a structure of fibrous masses, like the sepiolite found in Ampandrandava, Madagascar. It may also be found in lumps in Eskişehir. The color of sepiolite when it occurs in compact lumps is white or cream- coloured with grey, green, rose or even crimson tones, depending on the degree of contamination. The specific gravity of sepiolite is 2 to 2.3 g/cm3. Thhree types of water molocules can be identified in sepiolite;. Zeolitik water. Crystal water. Hidroksil water The ideal structural formula of sepiolite according to the Nagy-Bradley model is the following: Si12 Mg9 O30 (OH)6 (OH2)4 6H20 Sepiolite therefore exhibits a fibrous structure composed of talc-like ribbons with two sheets of tetrahedral silica units, linked by means of oxygen atoms to a central sheet of magnesium such that the tetrahedral sheet of silicon is continuous, but tetrahedral sheet of silica is inverted after every six tetrahedral units. This unique structure imparts sepiolite a fibrous matrix with channels (3.6x10.6 °A) oriented in the longitudinal direction of the fibers. Such interior channels allows penetration of organic and inorganic ions together with solutes into the crystal structure of sepiolite. There have been an accelerated interest in recent years towards extending the utilization of sepiolite to a variety of diverse fields which utilizes its sorptive, rheological and catalytic properties. In particular, its great absorbent capacity is used in such applications as bleaching and clarifying agent, filter aid, absorbent and carrier of catalysts. Investigations on sepiolite have so far focused more on its sorptive properties and attempts have been made to increase its surface area. The objective of this study is to determine the adsorption mechanism of various anionic reagents onto sepiolite, an important clay mineral well known with its sorptive, rheological catalytical properties The sepiolite sample used in this study was received from Mayas Mining Co. in Sivrihisar, Turkey. This brown sepiolite was ground to minus 65 microns, and the surface area of this sepiolite was found to be 68 m2/g by means of BET method using nitrogen as adsorbent. The chemical composition of Sivrihisar sepiolite is given below (Table 1.). SDS (Ci2H25NaS04) was used as anionic surfactant and NaOH and HC1 for pH adjustment. Distilled and deionized water with a conductivity value of 2x1ü"6 mhos/cm was used in all experiments. Experiments were conducted at ambient temperature (20-22 °C) unless otherwise specified Zeta potential measurements were carried out by a Zeta meter 3.0 equipped with microprocessor unit. 200 mg sepiolite was conditioned in 100 ml distilled water for 10 min. and then kept stationary for 5 min in order to let particles settle. An Table 1. Chemical composition of Sivrihisar sepiolite. aliquot taken from the supernatant was placed in the cell and the average of about 6 to 10 particles was recorded. Adsorption tests were conducted in 20 or 40 ml glass vials. 500 mg of sepiolite sample was mixed in 10 cc or its multiples with a solid to liquid ratio of 0.05. The vials were shaken for 2 h on a shaker and centrhuged for 15 min. The supernatant was analysed by a two phase titration technique originally applied to anionic surfactants using dimidium bromide and disulfine blue as indicators The adsorption density was calculated by the following formula: T =(Q-Cr)a/S.1000 where Q and C represents the initial and residual surfactant concentrations in moles/1, S the amount of solid in grams, a the volume of the solution in ml, and T the adsorption density in mol/g. Surfactant a series of systematic adsorption test were conducted with original, heat treated, and acid treated sepiolite to understand the way anionic reagents interact with sepiolite. Sodium dodecylsulfat (SDS) surfaktan is used as adsorbate. The adsorption density of SDS on sepiolite was investigated as a function of conditioning time, pH, solid concentration, reagent concentration and temperature. The behavior of sepiolite in the presence of SDS was determined by zeta potential and surface tansion measurements. All these measurements reveal that sepiolite undergoes acid-base interaction around pH 8.5. Sepiolite attains an equilibrium pH value 8.5 in 2 min. at natural pH conditions. When the initial pH value of suspension is adjusted to 3.0, the equilibrium pH value of 8.5 is attained after approximately 10 min. This indicates that sepiolite is strongly acidic in character and undergoes acid-base reactions in the vicinity of pH 8.5. When the suspension pH is adjusted to 1 1, it comes down to 9.5 after 30 min. and to its equilibrium pH only after several hours. Mg2+ concentration increases significantly in the acidic pH region. Zeta potential measurements yielded an iep of about 3.2 and 6.6 for solids concentrations of 0.2% and 5% respectively. Increasing the solution temperature from 25°C to 60°C showed a decrease in adsorption. Similarly, heat treated and acid activated sepiolites, thought produced a four to five fold increase in surface areas, exhibited a decrase in absolute adsorption. Adsortion tests as a function of solid concentrations revals that a solid concentration of 50 mg/ml is optimum for sepiolite/SDS system. Adsorption tests conducted versus conditioning time yields an equilibrium at 15 minutes. However, considering the extreme conditions and complying with the studies conducted earlier, a conditioning time of 2 hours was selected for subsequent studies. Adsorption tests performed with sepiolite in the presence of SDS shows that a plateau is reached at 5,06. 10"3 M residual SDS concentration which corresponds to an adsorption density of 8,65. 10"7 M/m2. The parking area of SDS molecule on sepiolite is found out to be 192 °A2 which corresponds to a degree of coverage of 0=0,16. Sepiolite/SDS system also exhibits the precipitation of surfactant due to the interaction of Mg ions released from the solid and the SDS molecules. The presence of Mg(DDS)2 precipitate significantly contributes to the consumption of surfactant. Therefore, in addition to abstraction tests a series of precipitation tests were also performed to enable the determination of net adsorption : Adsorption = Abstraction - Precipitation The adsorption isoterms found in this manner (See Figure 1) exhibit platea region whereas the precipitation isotherms undergoes a maximum. The solubility product using the ionic strength and activity coefficients yield a value of 2,26. 10" 10 N 1.E"°5 F E £ 1,E-06 O z LLI Q 1.E-07 z o I- £ 1.E-08 O CO Û < 1.E-09 1.E-05 1.E-04 1.E-03 1.E-02 1.E-01 FİNAL KONSANTRATİON, M Figure 1. Abraction, Precipitation and Adsorption isotherm of SDS on Sepiolite at Natural pH Condition The zeta potential profile as a function of SDS concentration shows that the zeta potential increases as the concentration increases. This is in line with the adsorption results where there the positive sites are occupied by the anionic reagent. Adsorption tests conducted as a function of pH indicate that as the pH decreases the amount of magnesium released into the solution increases and this leads to increased precipitation in the acidic pH region. While the abstraction isoterm as a 1.E-06 CM £l,E-07 CO LU Q £l,E-08 O CO Q < 1.E-09 5 7 9 FİRST pH 11 13 Figure 2. Abraction, Precipitation and Adsorption isotherm of SDS on Sepiolite at Different pH Conditions function of pH indicates higher adsorption in the acidic pH, the adsorption isoterm indicates the oposite. This indicates the insensitivity of adsorption results to elektrostatic attraction (Figure 2.). The adsorption acid and heat activated sepiolite shows lower adsorption densities compared to the original sepiolite. This is attributed to the loss of zeolitic and bound water and the collopse of magnesium in the octahedral layer. Adsorption tests conducted as a function of temperature shows that adsorption decrease with increasing temperature. The adsorption results obtained in this study have been fit into various models such as Langmuir, Flory-Huggins, Frumkin and Modified Frumkin. The best fit was obtained with the Modified Frumkin Model. The free energy of adsorption was obtained as 13-14 kJ/M. The heat of adsorption calculated using the Classius Clapeyron Equation comes out to be -1,87 Kcal/M indicating the role of physical adsorption in the system. A mechanism is proposed which involves a hydrogen bond between the O" of dodecylsulfate and the zeollitic or bound water in the sepiolite structure. The presence of Mg(DDS)2 association is also responsible for part of the adsorption particularly in the second region of the isotherm
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Adsorpsiyon; Reaktörler; Sepiyolit; Sepiyolit; Adsorption; Reactors; Sepiolite; Sepiolite